Structural health monitoring, photogrammetry & DIC. proceedings of the IMAC, a Conference and Exposition on Structural Dynamics 2018 /: proceedings of the IMAC, a Conference and Exposition on Structural Dynamics 2018. Volume 6 (c2019) - Unknown
No abstract available